1991
DOI: 10.1523/jneurosci.11-07-02135.1991
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ion channels and mutational effects in giant Drosophila neurons differentiated from cell division-arrested embryonic neuroblasts

Abstract: A culture system of "giant" Drosophila neurons derived from cytokinesis-arrested embryonic neuroblasts was developed to overcome the technical difficulties usually encountered in studying small Drosophila neurons. Cytochalasin B-treated neuroblasts differentiated into giant multinucleated cells that displayed neuronal morphology and neuron-specific markers (Wu et al., 1990). Here, we report that these giant neurons express different excitability patterns and membrane channels similar to those reported in excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 52 publications
9
139
1
Order By: Relevance
“…In all investigated cell types, the current waveforms and physiological properties of I Ca were typical for voltage-activated Ca 2ϩ currents and in the range of other insect preparations [A. mellifera, antennal motorneurons (Kloppenburg et al, 1999a) and Kenyon cells (Schäfer et al, 1994); D. melanogaster, embryonic neurons (Byerly and Leung, 1988;Saito and Wu, 1991); Gryllus bimaculatus, giant interneurons (Kloppenburg and Hörner, 1998); P. americana, embryonic cockroach neurons (Benquet et al, 1999) and DUM neurons (Wicher and Penzlin, 1994); Manduca sexta, motor neurons (Hayashi and Levine, 1992); S. americana, thoracic neurons (Laurent et al, 1993); Schistocerca gregaria, DUM neurons (Heidel and Pflüger, 2006) and thoracic neurons (Pearson et al, 1993)]. However, a quantitative comparison of the functional properties from I Ca between the different cell types revealed significant differences in some physiologically important parameters (for summary, see supplemental Table 1, available at www.jneurosci.org as supplemental material).…”
Section: Differences Of I Ca Between Cell Typesmentioning
confidence: 84%
See 1 more Smart Citation
“…In all investigated cell types, the current waveforms and physiological properties of I Ca were typical for voltage-activated Ca 2ϩ currents and in the range of other insect preparations [A. mellifera, antennal motorneurons (Kloppenburg et al, 1999a) and Kenyon cells (Schäfer et al, 1994); D. melanogaster, embryonic neurons (Byerly and Leung, 1988;Saito and Wu, 1991); Gryllus bimaculatus, giant interneurons (Kloppenburg and Hörner, 1998); P. americana, embryonic cockroach neurons (Benquet et al, 1999) and DUM neurons (Wicher and Penzlin, 1994); Manduca sexta, motor neurons (Hayashi and Levine, 1992); S. americana, thoracic neurons (Laurent et al, 1993); Schistocerca gregaria, DUM neurons (Heidel and Pflüger, 2006) and thoracic neurons (Pearson et al, 1993)]. However, a quantitative comparison of the functional properties from I Ca between the different cell types revealed significant differences in some physiologically important parameters (for summary, see supplemental Table 1, available at www.jneurosci.org as supplemental material).…”
Section: Differences Of I Ca Between Cell Typesmentioning
confidence: 84%
“…5B). This is a relatively low activation threshold compared with I Ca in uPNs and in many other insect neurons (Byerly and Leung, 1988;Saito and Wu, 1991;Hayashi and Levine, 1992;Laurent et al, 1993;Pearson et al, 1993;Schä-fer et al, 1994;Wicher andPenzlin, 1994, 1997;Kloppenburg and Hörner, 1998;Benquet et al, 1999;Kloppenburg et al, 1999a;Heidel and Pflüger, 2006). In type II LNs, despite the similar activation threshold in both LN types, the half-maximal voltage for activation is significantly more hyperpolarized than in type I LNs (Fig.…”
Section: Voltage-activated Camentioning
confidence: 92%
“…A null mutation in the slo locus strikingly alters the electrical properties of both neurons and muscles (22)(23)(24), affecting neurotransmitter release (25) and thereby causing a variety of behavioral defects among those in courtship behavior (26)(27)(28). We have previously demonstrated that a slo null mutant is behaviorally arrhythmic under free-running [constant darkness (DD)] conditions (13).…”
mentioning
confidence: 99%
“…The steady-state inactivation that was determined here (range 6%-20%) is typical of the delayed-rectifier K + current (Saito and Wu 1991;Alshuaib and Mathew 1998). Although the majority of cells did not display the transient A-type current, pharmacological experiments were carried out to test whether 4-AP affects the difference in K + current between the two genotypes.…”
Section: Reduced Ik Dr In Rutabagamentioning
confidence: 87%
“…For this reason, we focused mainly on the delayed-rectifier K + current. We applied a voltage protocol that maximizes the delayed-rectifier K + current and diminishes the A-type K + current (holding potential, −80 mV; test pulses, −40 to +60 mV) (Byerly and Leung 1988;Saito and Wu 1991;Alshuaib and Mathew 1998). IK DR was clearly activated at 0 mV, but only weakly activated at −20 mV in wild-type and rutabaga neurons.…”
Section: Comparison Of Ik Dr Inmentioning
confidence: 99%